Color Atlas of Local and Systemic Manifestations of Cardiovascular Disease. - Saksena, Franklin B. (John Wiley & Sons, 2008)
This brief guide to visual diagnosis helps the novice develop -- and the veteran refresh -- crucial skills that can spare the patient unnecessary testing and bring the physician one step closer to an accurate diagnosis. Dr Saksena draws on his years of experience in teaching and training to show you the physical signs of cardiovascular disease that can be spotted by visual examination. For each sign, a color photograph is paired with explanatory text that:.:.; describes the significant features of the sign.; explains its use in diagnosis.; identifies the likeliest causes. The book provides cor.